Developing environmental flow targets for benthic macroinvertebrates in large rivers using hydraulic habitat associations and taxa thresholds. (February 2023) - Wegscheider, Bernhard; Monk, Wendy A.; Lento, Jennifer; Haralampides, Katy; Ndong, Mouhamed; Linnansaari, Tommi; Allen Curry, R.
Highlights: Identification of indicator genera for flow provides important ecological information for large river benthic macroinvertebrate assemblages. Taxa Indicator Threshold Analysis was applied on benthic macroinvertebrate monitoring data in a large river in Eastern Canada Flow velocity was strongly associated with the distribution and relative abundance of benthic macroinvertebrates. Hydraulic-habitat thresholds and taxa associations were linked to alternative flow scenarios. Abstract: Holistic environmental flows frameworks are built on our understanding of key flow-ecology relationships that support sensitive taxa and critical ecosystem functions under different flow and water level scenarios. Most research on flow-ecology relationships has typically focused on small systems, with less known about flow associations, indicator taxa, and environmental thresholds of assemblage change along hydraulic gradients of large non-wadeable rivers. We assessed benthic macroinvertebrate assemblage structure and applied Taxa Indicator Threshold ANalysis (TITAN) on biomonitoring data collected during a six-year period in the Wolastoq | Saint John River in Atlantic Canada. Flow velocity was strongly associated with the distribution and relative abundance of benthic macroinvertebrates in the river, and taxon associations reflected functional adaptations to flow. We identified 33 genus-level indicator taxa that were either positively or negatively associated with flow velocity. Weaker taxa responses were shown for the gradient in median substrate particle size where 22 negatively and positively responding taxa were identified. We predicted changes in indicator taxon abundance under different flow scenarios using a hydrodynamic model, and characterised the distribution and availability of suitable hydraulic habitat patches within a 20 km reach downstream of a large hydropower generating station. These observations set the stage for the development of ecologically-based flow targets to support holistic environmental flow management in large rivers.